FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDINGS PERUSAHAAN - Felicya Chindy Liunardi; Rousilita Suhendah (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research was conducted to determine the effect of growth opportunity, net working capital, and liquidity on cash holdings in Basic Industry and Chemicals companies listed on Indonesia Stock Exchange (IDX) in 2017-2019. This study uses multiple linear regression analysis helped by Eviews 11 program and Microsoft Excel 2016. This study uses fixed effect models, and uses 30 basic industry and chemicals companies as samples. The result of this study indicate that growth opportunity and net working capital have a positive effect on cash holdings, liquidity has no significant effect on company’s cash holdings.